2012
DOI: 10.1128/aem.02287-12
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Lactobacillus casei BL23 Sortases

Abstract: bSortases are a class of enzymes that anchor surface proteins to the cell wall of Gram-positive bacteria. Lactobacillus casei BL23 harbors four sortase genes, two belonging to class A (srtA1 and srtA2) and two belonging to class C (srtC1 and srtC2). Class C sortases were clustered with genes encoding their putative substrates that were homologous to the SpaEFG and SpaCBA proteins that encode mucus adhesive pili in Lactobacillus rhamnosus GG. Twenty-three genes encoding putative sortase substrates were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…However, in the exclusion and displacement assays other interactions may play a role, such as the affinity of P-particles for bacteria attached to the cultured cells, which may led to higher P-particle retention on the HT-29 surface. We showed that L. casei BL23 and E. coli Nissle 1917 were indeed binding to HT-29 cells (Figure 8), although the binding was low, as has been previously reported [42][43]. Under our conditions a better adhesion was detected in L. casei BL23 compared to E. coli Nissle 1917.…”
Section: Resultssupporting
confidence: 86%
“…However, in the exclusion and displacement assays other interactions may play a role, such as the affinity of P-particles for bacteria attached to the cultured cells, which may led to higher P-particle retention on the HT-29 surface. We showed that L. casei BL23 and E. coli Nissle 1917 were indeed binding to HT-29 cells (Figure 8), although the binding was low, as has been previously reported [42][43]. Under our conditions a better adhesion was detected in L. casei BL23 compared to E. coli Nissle 1917.…”
Section: Resultssupporting
confidence: 86%
“…LspA, of L. salivarius UCC118, is the fourth characterised sortase-dependent protein that also binds mucus and is known to mediate adhesion of this species to intestinal epithelial cells [109, 128]. Recent studies with L. casei BL23 sortases and SrtA mutants suggest that SrtA might be involved in adhesion of this strain to Caco-2 and HT29 cells [117]. Although most sortase-dependent proteins of lactobacilli seem to have mucus-binding capacity, not all of them have affinity to mucus components and the function of putative lactobacilli sortase-dependent proteins remains unclear [16].…”
Section: Lactobacilli and Host Interactions Involving Bacterial Cementioning
confidence: 99%
“…Genes encoding housekeeping sortase enzymes ( srtA ) have been identified in the genomes of LAB including L. acidophilus (Buck et al, 2005), Lactobacillus salivarius UCC118 (van Pijkeren et al, 2006), Lactobacillus johnsonii NCC533 (Denou et al, 2008), L. rhamnosus GG (Kankainen et al, 2009), Lactococcus lactis IL1403 (Dieye et al, 2010), Lactobacillus casei BL23 (Munoz-Provencio et al, 2012), L. plantarum (Remus et al, 2013), and Lactobacillus crispatus ST1 (Edelman et al, 2012). Additionally, genes encoding class C sortase proteins ( srtC ) have been identified in both L. rhamnosus GG (Kankainen et al, 2009) and L. casei BL23 (Munoz-Provencio et al, 2012). The genomic context of the srtA locus varies widely among species ( Figure 2A ); however, srtC genes have been found to cluster with their targets ( spa genes) as was observed in both L. rhamnosus GG ( Figure 2B ) and L. casei BL23 (Munoz-Provencio et al, 2012).…”
Section: Comparative Analysis Of Sortase In Labmentioning
confidence: 99%
“…Additionally, genes encoding class C sortase proteins ( srtC ) have been identified in both L. rhamnosus GG (Kankainen et al, 2009) and L. casei BL23 (Munoz-Provencio et al, 2012). The genomic context of the srtA locus varies widely among species ( Figure 2A ); however, srtC genes have been found to cluster with their targets ( spa genes) as was observed in both L. rhamnosus GG ( Figure 2B ) and L. casei BL23 (Munoz-Provencio et al, 2012). An unrooted phylogenetic tree shows the relationships between the sortase protein sequences identified in the aforementioned species of LAB as well as those present in other LAB species including L. lactis subsp.…”
Section: Comparative Analysis Of Sortase In Labmentioning
confidence: 99%